Blood donor deferral for men who have sex with men: the Blood Donation Rules Opinion Study (Blood DROPS). Issue 12 (22nd July 2015) - Custer, Brian; Sheon, Nicolas; Siedle‐Khan, Bob; Pollack, Lance; Spencer, Bryan; Bialkowski, Walter; D'Andrea, Pam; Sullivan, Marian; Glynn, Simone; Williams, Alan; ,
Abstract : BACKGROUND: In the United States, any man who discloses having had sex with another man (MSM) even once since 1977 is currently deferred from donating blood. A study was conducted to assess noncompliance with the policy at four geographically dispersed blood centers. STUDY DESIGN AND METHODS: Male donors 18+ years of age with e‐mail addresses were randomly selected and invited to complete a confidential online survey between August and October 2013. No additional recruitment e‐mails were sent. Survey content included demographics, sexual history, donation history, compliance with the policy, and opinions about current and modified policies. RESULTS: Response rate was 11.5% but varied by center (6.3% to 21.7%). Of 3183 completed surveys, 2.6% of respondents (95% confidence interval, 2.1%‐3.2%) reported donation after male–male sex. Noncompliance was not statistically different among the centers (p = 0.1), but was related to age with 5.7, 4.6, 2.5, and 1.0% of donors 18 to 24, 25 to 34, 35 to 54, and 50+ years of age, respectively, reporting noncompliance (p < 0.001). Of all respondents, 6.8% reported at least six female and 0.3% reported at least six male sex partners in the past 5 years. Opinions about the current MSM policy were mixed with noncomplying donors more supportive of change than complying donors. Approximatey half of noncompliers indicated they would adhere to a 1‐year deferral. CONCLUSION: Noncompliance with the MSM policy is evident and may be increasing compared to earlier data. Any change from the current policy will require close monitoring to determine whether it affects residual risk of HIV in the US blood supply.